A Klebsiella-phage cocktail to broaden the host range and delay bacteriophage resistance both in vitro and in vivo - Huanchang Chen; Haifeng Liu; Yanchun Gong; Rhys A. Dunstan; Zhexiao Ma; Cui Zhou; Deyi Zhao; Miran Tang; Trevor Lithgow; Tieli Zhou (npj Biofilms and Microbiomes)
Abstract Bacteriophages (phages), viruses capable of infecting and lysing bacteria, are a promising alternative for treating infections from hypervirulent, antibiotic-resistant pathogens like Klebsiella pneumoniae, though narrow host range and phage resistance remain challenges. In this study, the hypervirulent K. pneumoniae NTUH-K2044 was used to purify phage ΦK2044, while two ΦK2044-resistant strains were used to purify two further phages: ΦKR1, and ΦKR8 from hospital sewage. A detailed characterization showed that ΦK2044 specifically killed KL1 capsule-type K. pneumoniae, while ΦKR1 and ΦKR8 targeted 13 different capsular serotypes. The phage cocktail (ΦK2044 + ΦKR1 + ΦKR8) effectively killed K. pneumoniae in biofilms, pre-treatment biofilm formation, and delayed phage-resistance. The phage cocktail improved 7-day survival in Galleria mellonella and mouse models and showed therapeutic potential in a catheter biofilm model. In summary, this proof-of-principle phage cocktail has a broad host range, including hypervirulent and highly drug-resistant K. pneumoniae, and serves as a promising starting point for optimizing phage therapy.